Effectiveness of Giving Green Bean Juice (Vigna Radiata) to Increase Breast Milk Production for Postpartum Mothers in North Tapanuli Regency in 2023 - Janner Pelanjani Simamora; Naomi Isabella Hutabarat; Dimpu Rismawaty Nainggolan (Postgraduate, University of Mataram, 2023)
The quantity and quality of a mother's food greatly influences the amount of breast milk produced. Mothers who breastfeed are strongly encouraged to obtain additional nutrition for breast milk production and maternal energy. One of them is green beans as a food that is useful for facilitating breast milk production. This research aims to analyze the effectiveness of giving green bean juice (vigna radiata) to increase breast milk production for postpartum mothers in North Tapanuli Regency in 2023. This research is a type of quantitative research. The design used in this research is a quasi-experimental design using a pre-test and post-test nonequivalent control group approach. The results of statistical research with Mann Whitney showed that there was an average difference (mean) between the control group and the intervention group before consuming green bean juice and after consuming green bean juice 8.54. The results of the analysis using the Mann-Whitney Test showed that there was a significant difference between postpartum mothers in the treatment group (given Green Bean Juice) and postpartum mothers in the control group in terms of increasing breast milk production for postpartum mothers with a p-value of 0.007